A novel approach to sustainable water treatment utilising Cocos nucifera and Luffa acutangula - Ganesan Ramachandran; Latha Asaithambi; Partheeban Pachaivannan; G. Venkatesan (Desalination and Water Treatment)
Water quality depends on Total Dissolved Solids (TDS), an indicator of harmful pollutants in the water. Therefore, the primary goal of the study is to eliminate TDS utilising the new Cocos nucifera and Luffa acutangula natural filtering technique. The parameters analyzed such as pH, turbidity, hardness, calcium, chloride, sulphate, TDS, TSS, iron, and copper and SEM and FTIR examination were performed. After water treatment, the TDS removal percentage of novel Cocos nucifera is 45.84 %, and Luffa acutangula is 53.94 %. A significance threshold of 0.001 was used while doing regression analysis with SPSS software (P < 0.05). The mean TDS values of groups 1 and 2 are 458.18 mg/L and 389.56 mg/L, respectively. Similarly, the standard deviation is 3.820 and 7.328, respectively. The novel Luffa acutangula performs better TDS removal than Cocos nucifera, which is better than the conventional method of TDS removal from water.